Padrões distintos de congruência climática em duas espécies invasoras de prosopis em zonas semi-áridas da América do Sul - Oliveira, Brunno Freire Dantas de (2012)
Based on climate data and occurrence records, ecological niche models (ENM) are an important opportunity to identify areas at risk or vulnerable to biological invasion. These models are based on the assumption that there is a match between the climatic characteristic of native and invaded regions predicting the potential distribution of exotic species. Using new methods to measure niche overlap, we chose two exotic species fairly common in semi-arid regions of South America, Prosopis juliflora (Sw.) D.C. and Prosopis pallida (H. ; B. ex. Willd) HBK, to test the climate matching hypothesis. Our results indicate that both species occur with little niche overlap in the native region while the inverse pattern is observed in the invaded region on South America, where both species occur with high climatic overlap. Maybe some non-climate factor act limiting the spread of P. pallida on the native range. We believe that a founder effect can explain these similarities between species niche in the invaded region once the seeds planted in Brazil came from a small region on the Native range (Piura in Peru), where both species occur sympatric. Our hypothesis of a founder effect may be evident when we look at the differences between the predictions of the models built in the native and invaded ranges. Furthermore, our results indicate that P. juliflora shows high levels of climate matching between native and invaded ranges. However, conclusions about climate matching of P. pallida should be taken with caution. Our models based on climatic variables provide multiple locations suitable for occurrence of both species in regions where they still don t have occurrence records, including places of high interest for conservation.